1986
DOI: 10.1128/jvi.57.1.285-293.1986
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies against Aleutian disease virus distinguish virus strains and differentiate sites of virus replication from sites of viral antigen sequestration

Abstract: Monoclonal antibodies (mAbs) were used to study antigenic differences among strains of Aleutian disease virus (ADV) and to characterize viral proteins in vitro and in vivo. A number of ADV field strains could be discriminated, and highly virulent Utah I ADV was clearly delineated from the tissue culture-adapted avirulent ADV-G strain. This specificity could be demonstrated by indirect immunofluorescence against infected cultures of Crandell feline kidney cells or against tissues of Utah I ADV-infected mink. Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 35 publications
2
25
0
Order By: Relevance
“…The intranuclear shells of VP were not resolved in previous studies in which the same anti-VP MAbs were used for immunofluorescence analysis (3,32). The hollow shell structures that are so striking in single confocal optical sections appear more as solid bodies when viewed by epifluorescence.…”
Section: Panel a [Ns] With Panel B [Dna]mentioning
confidence: 92%
See 1 more Smart Citation
“…The intranuclear shells of VP were not resolved in previous studies in which the same anti-VP MAbs were used for immunofluorescence analysis (3,32). The hollow shell structures that are so striking in single confocal optical sections appear more as solid bodies when viewed by epifluorescence.…”
Section: Panel a [Ns] With Panel B [Dna]mentioning
confidence: 92%
“…The rabbit anti-NS immunoglobulin G (27,31) was conjugated to fluorescein isothiocyanate. A cocktail of murine monoclonal antibodies reactive against both VP1 and VP2 was used to detect ADV VP proteins (32). DNA probes for the detection of ADV DNA were prepared by PCR (29).…”
mentioning
confidence: 99%
“…According to previous immunohistological findings (PORTER et al, 1969;RACE et al, 1986;HAAS et al, 1990) viral antigen was found in the cytoplasm of Kupffer cells. A prerequisite for the demonstration of viral proteins was to perform an elution procedure on cryosections.…”
Section: Discussionmentioning
confidence: 65%
“…Viruses and viral DNA. The propagation of the pathogenic strains ADV-Utah 1 (12, 15) and 16,37) in infected mink and the preparation of partially purified virus from organs were done by published procedures (2,12,37). The preparation of single-stranded virion DNA from partially purified strains ADV-Utah I and ADV-Pullman was (10,29) is also shown.…”
Section: Methodsmentioning
confidence: 99%
“…Comparison of ADV strains has been limited to date but has suggested that the various strains are very similar (1,9,35,37). A major problem in direct molecular comparison relates to the difficulty in growing virulent virus isolates in cell culture.…”
mentioning
confidence: 99%